Effect of pre-bypass methylprednisolone on post-operative renal function following correction of atrial septal defect under cardiopulmonary bypass - Dhar, S; Rahman, Z; Hasan, K; Hoque, MF; Sultana, A (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):72-79 The abstract of this article is available on the PubMed website